KAEDAH-KAEDAH HUKUM KEBIASAAN INTERNASIONAL YANG BERLAKU DALAM KONTRAK BISNIS INTERNATIONAL - Cindawati, Cindawati (Faculty of Law, University of Palembang, 2018)
The objective of the study is to analyze and describe the international customary laws applicable in international business contracts. Normative juridical research method. International Customary Law, is a legal source that can be regarded as the source of law first born in the International Trade Law of the repetitive practice of traders, in such a way that repetitive habits with such long time become binding. A customary practice of becoming binding must meet the following conditions: A practice which is repeatedly followed and followed by more than two parties (state practice): This practice is accepted as binding (opnio iuris sive necessitatis). For example, a codified habit in a freight contract is one example of FOB (Free On Board). Research result: Incoterms was established to provide a universal standard definition of terms used in national and international business transactions such as: FOB (Free On Board).